REHABILITASI MANGROVE BERBASIS EDUKASI BERSAMA SISWA SMK PERIKANAN DUMAI TAHUN 2024 - Nabila Afifah Azuga; Sefni Hendris; Ilham Ilahi; Benny Heltonika; Dessy Yoswaty; Irvina Nurrachmi; Nursyirwani Nursyirwani; Yusni Ikhwan Siregar (LPPM Universitas Abdurrab, 2025)
Coastal abrasion in Purnama Sub-district, Dumai City, Riau Province is considered severe, with erosion exceeding 3 meters per year. This situation calls for urgent mangrove rehabilitation as an ecological mitigation effort. This community service activity involved 100 students from Dumai Fisheries Vocational High School, along with lecturers and students from the Belukap Mangrove Club (BMC), Department of Marine Science, University of Riau. The program consisted of two stages: classroom-based education on mangrove ecosystem functions, coastal conservation, and planting techniques; followed by the planting of 500 Rhizophora apiculata seedlings in the Purnama Mangrove Forest. From the evaluation results showed an increase in students' average knowledge scores over 25.7%. Participation was also high: 100% attendance and documentation, 85% engagement in discussions, and 95% in the planting activity. Students expressed positive perceptions, particularly regarding the hands-on learning experience and their increased understanding of mangrove importance. These results suggest that combining environmental education with field practice effectively enhances awareness and builds students’ capacity in coastal conservation. Collaboration among academics, vocational schools, communities, and local government was a key factor in the program’s success and offers a replicable model for similar initiatives. This program supports the achievement of Sustainable Development Goals (SDGs) 4 and 13, focusing on quality education and climate change adaptation.